Happiness instrument development - Lukman@Zawawi, Mohamad; Ateerah, A.R. (2019)
Happiness is related with subjective well being. However, there is scarce of research pertaining to Islamic view of happiness. Previous research from Western perspectives have proven that positive element and attitude contribute positively to happiness. Hence, this research tries to identify several aspects that have relationship with happiness among Muslim specifically. Happiness Instrument was developed based on al-Ghazali’s concept of happiness. It was about 500 Muslims involved in this study quantitatively in which using developed scale inventory as the main instrument. The data collected from the sampled population has been descriptively analysed based on mean and SD attained from the responses. Moreover, the PLS-SEM has been utilized in this chapter to test the theoretical model. Coherently, multiple approaches have been incorporated to examine the measurement and structural models such as the convergent validity, discriminant validity, R-square, and Fsquare among others. As a result, there is significant result of the construct such as religious knowledge, practices and individual with happiness.